Ethnic discordance in serum anti-Müllerian hormone in European and Indian healthy women and Indian infertile women. Issue 5 (November 2022) - Gromski, Piotr S.; Patil, Rajendra Sadashiv; Chougule, Shruti Mahesh; Bhomkar, Deepali Atul; Jirge, Padma Rekha; Nelson, Scott M.
Abstract: Research question: Does anti-Müllerian hormone (AMH) differ between healthy European and Indian women, and are potential ethnic differences modified by infertility diagnosis? Design: Cross-sectional analysis of three prospectively recruited cohorts ( n = 2758); healthy European women ( n = 758), healthy community cohort from Kolhapur, India ( n = 400) and infertility cohort from Kolhapur, India ( n = 1600). AMH was determined by assay. Ethnicity, age and cause of infertility were modelled using additive quantile regression models. Results: Healthy Indian women had lower AMH than their healthy European counterparts (population estimates 20.0% lower [95% CI 7.2–36.5]), with increasing discordance with increasing age; at 25 years AMH was 11.9% lower (95% CI 9.4–14.1), increasing to 40.0% lower (95% CI 0–64.6) by age 45. Comparison of healthy and infertile Indian women revealed differences that were related to cause of infertility. Women whose male partner had severe oligoasthenoteratozoospermia ( n = 95) had similar AMH to controls; women with polycystic ovary syndrome ( n = 220) had higher AMH, especially in those <30 years, and in women with a principal diagnosis of unexplained infertility ( n = 757) AMH was lower (median difference 22.6% lower; 95% CI 9.1–37.7) than controls. Conclusions: AMH is substantially lower in healthy Indian women at all ages than their European counterparts. Infertile Indian women have variable differences in AMH from healthy Indian controls, with the extent and direction of differences primarily reflecting the underlying cause of infertility. Recognition of ethnic and cause-specific differences are critical to ensure accurate contextualizing of results and clinical outcomes for patients.